A bifailure specimen for accessing failure criteria performance. (August 2015) - Driemeier, Larissa; Moura, Rafael T.; Machado, Izabel F.; Alves, Marcilio
Abstract: Many engineering ductile materials, such as metals, show inelastic behavior with corresponding large deformations. For these materials, the prediction of failure, defined as local material separation, is still nowadays a scientific challenge. Failure initiation, its locus and evolution, has been discussed extensively in recent literature. This work presents a bifailure specimen, especially developed to evaluate failure criteria at high and low triaxiality. In order to explore further the failure phenomenon, uncoupled models are numerically implemented in an explicit finite element code. Simulations were performed and do indicate that, for the studied examples, uncoupled models are not capable of correctly predicting failure. Highlights: Failure initiation, its locus and evolution, has been discussed extensively in recent literature. The current work does an indepth analysis of the performance of some well known sudden failure criteria. An ad hoc specimen, designed to generate two distinct failure modes, is proposed. None of adopted sudden failure criteria showed satisfactory performance for the proposed specimen.